Government of Karnataka Public Financial Management Reform Action Plan, 2014, Volume 2. Appendix - World Bank (Washington, DC, 2014)
The main report comprises the following chapters: executive summary provides the overall view of the reform action plan. Chapter one outlines the background, scope and methodology for the study; chapter two outlines the overview of the state finances; chapter three describe the accomplishments made against the 2004 agreed PFMA action plan; chapter four provides an overview of the analysis, gaps and recommendations made in the study; chapter five describes the way forward for implementation of the action plan; annex one: PFM reform action plan - 2014 contains a thematic-wise plan outlining the actions to be taken, the responsible department for the actions, and the expected timeframe for completing the actions. The detailed analysis of the issues and the logic for the action plan are provided in the respective sections of the appendix; annex two: 2004 PFMA action plan, outlines the current status of action taken on 2004 PFMA action plan: this contains the action plan as proposed in the 2004 report, updated with the current status of actions in the identified areas. In case where the actions have been taken and completed by the Government of Karnataka, the impact has been documented. The appendix comprises the following sections: section one: theme one: strengthening PFM legal and institutional framework; section two: theme two: enhancing comprehensiveness and credibility of the budget; section three: theme three: strengthening accounting, reporting, controls, and transparency; section four: theme four: improving fiscal assets and liability management system; section five: theme five: strengthening audit and legislative oversight; section six: theme six: improving PFM in local self-governments; section seven: theme six: improving PFM in public sector undertakings (state owned); each section describes the various areas of public financial management in the Government of Karnataka grouped into thematic reform areas. Each reform area has a discussion of the background, the reform actions proposed in the 2004 PFMA action plan, the progress of reforms over the last decade, the issues presently identified, and the rationale for the reform actions proposed; and section eight: 2014 action plan: this section describes the action plan with next steps to be followed under each activity of the action plan.